2010
DOI: 10.1016/j.jog.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frictional heating and thermal advection on pre-seismic sliding: a numerical simulation using a rate-, state- and temperature-dependent friction law

Abstract: a b s t r a c tLaboratory experiments on simulated faults in rocks clearly show the temperature dependence of dynamic rock friction. Since rocks surrounding faults are permeable, we have developed a numerical method to describe the thermo-mechanical evolution of the pre-seismic sliding phase which takes into account both the rate-, state-and temperature-dependent friction law and the heat advection term in the energy equation. We consider a laminar fluid motion perpendicular to a vertical fault plane and assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…[3] Theoretical studies have focused on thermal pressurization (TP) as an important slip-weakening mechanism, at both the coseismic slip [Lachenbruch, 1980;Mase and Smith, 1985;Rice, 2006] and rupture nucleation [Segall and Rice, 2006;de Lorenzo and Lpddo, 2010] of an earthquake. Other high-velocity slip-weakening mechanisms include silica gel lubrication [Di Toro et al, 2004], bulk melting [Tsutsumi and Shimamoto, 1997;Hirose and Shimamoto, 2005], flash heating [Rice, 1999], and nanoparticle lubrication [Han et al, 2010;Reches and Lockner, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Theoretical studies have focused on thermal pressurization (TP) as an important slip-weakening mechanism, at both the coseismic slip [Lachenbruch, 1980;Mase and Smith, 1985;Rice, 2006] and rupture nucleation [Segall and Rice, 2006;de Lorenzo and Lpddo, 2010] of an earthquake. Other high-velocity slip-weakening mechanisms include silica gel lubrication [Di Toro et al, 2004], bulk melting [Tsutsumi and Shimamoto, 1997;Hirose and Shimamoto, 2005], flash heating [Rice, 1999], and nanoparticle lubrication [Han et al, 2010;Reches and Lockner, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Motion on large, upper crustal fault zones is governed in large part by the evolution of temperature and pore fluid pressure within cataclasites (for example Rice, 1992Rice, , 2006Blanpied and others, 1998;de Lorenzo and Loddo, 2010;De Paola and others, 2011;Goren and others, 2010). However, observations that constrain the temperature of cataclastic deformation in natural faults, and the origin and evolution of syntectonic pore fluids, are relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…These coatings show sustained friction coefficient values as low as 0.02 in water-glycol-based lubricants, and offer a unique combination of excellent wear resistance and low friction when combined with the high hardness of the mixed-phase composite (30)(31)(32)(33)(34)(35).…”
Section: Technologies For Super-low Friction and Wear Resistancementioning
confidence: 99%
“…It was found that the cumulative distribution function of the recurrence intervals of simulated earthquakes at each segment approximately obeys a Brownian passage time distribution or a lognormal distribution. Later on, using a rate-, state-, and temperaturedependent friction law, a numerical method was developed to investigate the effects of frictional heating and thermal advection on pre-seismic sliding [34].…”
Section: Application Of Lifecycle Assessment (Lca) To Tribological Tementioning
confidence: 99%